Ontogeny of horizontal movement patterns of rehabilitated grey seal juveniles (Halichoerus grypus) in the Baltic Sea - Kuncienė, Laura; Nachtsheim, Dominik; Siebert, Ursula; Kleiva, Žilvinas (Frontiers in Marine Science, 2024)
The ethical considerations and scepticism over the ecological benefits have fuelled debate about the rehabilitation of wildlife. Although there is evidence that many rehabilitated species are able to survive after rehabilitation, there is a paucity of research on the behaviour of rehabilitated pinnipeds, including grey seals (Halichoerus grypus). In this study, 14 rehabilitated grey seal juveniles were equipped with biotelemetry devices in order to conduct remote post-release monitoring and to investigate ontogeny of their movements in the Baltic Sea. The study revealed that their movements were similar to wild, non-rehabilitated grey seal pups when leaving their natal site: at first, they exhibited highly exploratory behaviour with largely transient movements, then switched into a resident movement pattern, while maximising foraging and minimising travelling time. Neither sex nor year of release, which varied in terms of rehabilitation time and body mass, had a significant effect on the ontogeny of these movements. Movements were significantly influenced by the time after release, suggesting that rehabilitated juveniles have gained experience and developed their movements over time in order to survive in the wild.